A Concise Study on Teachers’ Perceptions of Their Continuing Professional Development in Cambodian High Schools - Kassy Sey (MASI Mandiri Edukasi, 2023)
This concise study was mainly about the perceptions of teachers toward continuing professional development (CPD). A qualitative method was employed to gather participants' information and ideas. Two-main questions and several sub-questions were designed to interview the respondents to address the research issue. Findings suggested that continuing professional development (CPD) is essential for teachers and school leaders to develop their mindsets and growth; moreover, most respondents agreed that CPD is crucial for self-development. However, one respondent felt that the school lacked teacher training. This can be notified that school leaders shall create more CPD activities for improving their colleagues. Moreover, without continuing professional development (CPD), teachers and staff will not become well-educated and knowledgeable human resources. Hence, lifelong Learning is a must for oneself to be promoted or to a successful life journey. Last but not least, this study implied that school leaders' and teachers’ perceptions were slightly different regarding CPD. Further study shall focus on teachers’ satisfaction regarding continuing professional development (CPD).